Hydrogen sulfide oxidation - Malagrinò, Francesca (2019)
Hydrogen sulfide (H2S), a known inhibitor of cytochrome c oxidase (CcOX), plays a key signaling role in human (patho)physiology. H2S is synthesized endogenously and mainly metabolized by a mitochondrial sulfide-oxidizing pathway including sulfide:quinone oxidoreductase (SQR), whereby H2S-derived electrons are injected into the respiratory chain stimulating O2 consumption and ATP synthesis. Under hypoxic conditions, H2S has higher stability and is synthesized at higher levels with protective effects for the cell. Herein, working on SW480 colon cancer cells, we evaluated the effect of hypoxia on the ability of cells to metabolize H2S. The sulfide-oxidizing activity was assessed by high-resolution respirometry, measuring the stimulatory effect of sulfide on rotenone-inhibited cell respiration in the absence or presence of antimycin A. Compared to cells grown under normoxic conditions (air O2), cells exposed for 24 h to hypoxia (1% O2) displayed a 1.3-fold reduction in maximal sulfide-oxidizing activity and 2.7-fold lower basal O2 respiration. Based on citrate synthase activity assays, mitochondria of hypoxia-treated cells were 1.8-fold less abundant and displayed 1.4-fold higher maximal sulfide-oxidizing activity and 2.6-fold enrichment in SQR as evaluated by immunoblotting. We speculate that under hypoxic conditions mitochondria undergo these adaptive changes to protect cell respiration from H2S poisoning.